FAKTOR-FAKTOR KARAKTERISTIK PERAWAT DALAM MELAKSANAKAN DOKUMENTASI ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RUMAH SAKIT MITRA KASIH - Sumiati, Pipit; Suryani, Melyati (Jurnal Kesehatan & Disiplin Ilmu, 2025)
This study aims to determine the external factors in the implementation of nursing care documentation in the inpatient room of Mitra Kasih Cimahi Hospital. This study used a quantitative descriptive design, involving some nurses in the inpatient room of 37 respondents and 37 nursing care documentation. Results. The results showed that 37 nurses (100%) who performed nursing care documentation were included in the early adulthood category with most of the 33 people (89.2%) having a D3 Nursing education, 20 people (54.1%) had a good level of knowledge, 19 people (51.4%) had a positive attitude, 25 people (67.6%) had moderate motivation, and 19 people (51.4%) did complete documentation. There is regular evaluation with standardized standards and feedback so that nurses know the successes and shortcomings in writing and feel cared for by superiors directly.